DNA Landscape Creation And Its Characterization Via Scaling Laws - T, Umadevi (2007)
In this work, we consider genomic code of bacteria, Streptomyces coelicolor. A DNA landscape is created from the DNA sequence. This DNA sequence was made available from the gene data bank.